Mechanical and Corrosion Properties of Magnesium-Bioceramic Nanocomposites - Kowalski K. (Archives of Metallurgy and Materials, 2016)
Magnesium alloys have recently attracted much attention as a new generation of biodegradable metallic materials. In this work, Mg1Mn1Zn0.3Zr-bioceramic nanocomposites and their scaffolds were synthesized using a combination of mechanical alloying and a space-holder sintering process. The phase and microstructure analysis was carried out using X-ray diffraction, scanning electron microscopy and the properties were measured using hardness and corrosion testing equipment. Nanostructured Mg-bioceramic composites with a grain sizes below 73 nm were synthesized. The Vickers hardnesses for the bulk nanostructured Mg-based composites are two times greater than that of pure microcrystalline Mg metal (50 HV0.3). Produced Mg-based bionanomaterials can be applied in medicine.